Governance of the urban water circular economy - Canh D Nguyen; Thuan M Tu; Tu M Nguyen; Ashok Sharma; Gopalakrishnan Kumar; Quan H Nguyen (Current Opinion in Environmental Sustainability, 2026)

From bench to bedside: stem cell therapy as a transformative approach against HIV - Ankit Kumar Bharti S; Anirban Goutam Mukherjee; Abilash Valsala Gopalakrishnan; Babu Gajendran; Rahul Vashishth; Sabina Evan Prince (Molecular Biology Reports, 2026)

RNA modifications as determinants of cancer cell death: from epitranscriptomic mechanisms to therapeutic targeting - Anirban Goutam Mukherjee; Ankit Kumar Bharti; Deepthi Maria Mathew; Bhavani Manoj Varma; Sristy Pradhan; Abilash Valsala Gopalakrishnan (Functional & Integrative Genomics, 2026)

Exploratory GC–MS profiling of solvent-extractable compounds from different body regions of Oecophylla smaragdina workers - Selvam Kulanthaivelu; Shiva Nagendran; Edula Uday Kumar; Arumugam Gopalakrishnan Meena; Sivakumar Palraj (Toxicon, 2026)

Towards climate-resilient rice (Oryza sativa L.): re-engineering root system architecture for abiotic stress tolerance: a review - Prem kumar Ajmeera; Manonmani Swaminathan; Gopalakrishnan Chellappan; Sritharan Natarajan; Rajeswari Sivakami (Euphytica, 2026)

Sono-electrochemical immersion as a non-antibiotic prophylactic strategy enhances microbial control, immunity, and survival in mud crab (Scylla serrata) under habitat-enhanced recirculating aquaculture systems (RAS) - Jowin T James; Naveen Nivas S; Dinesh Kaippilly; Dung Le Viet; Geeji MT; Subi S; Ayyaru Gopalakrishnan; Anandanatesan Arundathy; Sanjay Kumar S; Alwin Peter M; Jebaraj H; Sneha Suresh; et al. (Aquacultural Engineering, 2026)

Impact of emerging contaminants on inhibited steady-state anaerobic digestion: a review of the fate and degradation characteristics of antibiotics, PFAS, and microplastics - Sharareh Harirchi; Mandana Lak; Kenan Dalkilic; Lydia Mawar Ningsih; Abdullah Bilal Ozturk; Aytac Perihan Akan; Nguyen Duc Canh; Mohammad J. Taherzadeh; Gopalakrishnan Kumar (Reviews in Environmental Science and Bio/Technology, 2026)

Life cycle assessment for circular biomanufacturing of lactic acid from sugarcane bagasse - Kumar Raja Vanapalli; Naseeba Parveen; Sunil K. Maity; Roberto Parra Saldivar; Samuel Jacob; Gopalakrishnan Kumar; Vinod Kumar (Sustainable Production and Consumption, 2026)

Time-resolved co-transport dynamics of microplastics and antibiotic resistance genes during stormwater first flush - Taehwan Lee; Hongmok Jo; Min-Sang Kim; Yeongmi Park; Uijeong Han; Jaehun Gwon; Seon-Young Kim; Seunghyun Lee; Ran Kim; Hyoyoung Lee; Gopalakrishnan Kumar; Si-Kyung Cho (Environmental Research, 2026)

A Spatial Decision Support System for Coastal Inundation Risk Atlas - A Immanuel; Mayamanikandan Thangavelu; Sujith Kumar Saka; Gopinath Gopalakrishnan; Sisir Kumar Dash; Tune Usha (Journal of the Indian Society of Remote Sensing, 2026)

Nitrosamines in Pharmaceuticals and the Environment: Genotoxic Impurities, Detection Strategies, and Developmental Health Risks - Uday Shashikumar; Hem Nikhilesh Naik; Jayashree E. Veerabhadra; Vimalkumar Krishnamoorthi; Pei-Chien Tsai; Po-Chin Huang; Yi-Hsun Chen; Smita Jauhari; Yuan-Chung Lin; Vinoth Kumar Ponnusamy; Gopalakrishnan Kumar (Current Pollution Reports, 2026)

Climate Hazard Linked Adaptation Options for Soybean in South Asian Region – A Meta-Analysis - Boopathi Gopalakrishnan; Eshwarayya Bhavani; Venugopalan Visha Kumari; Niveta Jain; Nobin Chandra Paul; Aniket Deo; Roshan Babu Ojha; Chitiprolu Anantha Ramarao; Pramod Kumar Aggarwal (Journal of Soil Science and Plant Nutrition, 2026)

Ecosystem-based assessment of tropical Lobster Sea cage farming impact: A novel BACI-framework for sustainable mariculture expansion along the Northeast coast of Arabian Sea - Mayur Shivdas Tade; Suresh Kumar Mojjada; Abdul Azeez Pokkathappada; Prachi Siddharth Bagde; T.S. Ramshad; Mayank Soni; Aarsha Subramanian; Swathi Lekshmi Perumal Sundaram; Boby Ignatius; Suresh Vettath Raghavan; Achamveetil Gopalakrishnan; Damodaran Nair Divu (Aquaculture, 2026)

Forgotten fibre waste: Mycoremediation and recycling of used absorbent hygiene products - Roberto Parra-Saldívar; Stephen J. Russell; Hafiz M.N. Iqbal; Mireya Navarro-Márquez; Guadalupe Gutiérrez-Soto; Vinod Kumar; Gopalakrishnan Kumar; Kumar Raja Vanapalli; Sunil K. Maity (Resources, Conservation and Recycling, 2026)

Perfluorooctane sulfonate (PFOS) inhibits methane production during sludge anaerobic digestion by breaking the carbon-transfer bridge between methanogenesis and acidogenesis - Zhaobin Liu; Yijing Gao; Jiayi Wang; Xinyu Jing; Xue Chen; Weijie Hu; Xueqin Lu; Meng Liu; Xiaosong He; Gopalakrishnan Kumar; Guangyin Zhen (Bioresource Technology, 2026)

Reduction of ammonia accumulation in anaerobic digestion of chicken manure by co-digestion and biogas-stripping - Sneha Prakash Naik; Vinoth Kumar Ponnusamy; Gopalakrishnan Kumar; Cing-Hong Yang; Pei-Chien Tsai; Chiu-Yue Lin; Gunda Mohanakrishna; Chyi-How Lay (Bioresource Technology Reports, 2026)

Wavelet-Hermite Fractional Model for Ecological Interactions: for Advancing Climate Modeling and Ecosystem Dynamics - Khushbu Agrawal; E. A. Gopalakrishnan; K. V. Nagaraja; V. K. Chaurasiya; G. R. Naik; Ajay Kumar (Modeling Earth Systems and Environment, 2026)

Insights on recent baleen whale (Cetacea: Mysticeti) stranding events along the south-west coast of India - R. Ratheesh Kumar; T.G. Sumithra; U. Utthamapandian; V. Durga; S. Monolisha; Alvin Anto; S. Vinayak; K.V. Akhilesh; Grinson George; A. Gopalakrishnan (Regional Studies in Marine Science, 2025)

Polymer-based recyclable solid-phase optical sensor to quantify Hg2+ in aqueous samples - Sangeetha Krishna Kumar; Lingesh Gopalakrishnan; Prabhakaran Srinivasan; Deepan Kumar Madhu; Prabhakaran Deivasigamani; Akhila Maheswari Mohan (Environmental Research, 2025)

Spent Coffee Grains (SCG) to biofuels: a comparative techno-economic evaluation for hydrogen and methane production - Abdullah Bilal Ozturk; Natalija Jakovljevic; Georgeio Semaan; Gopalakrishnan Kumar (Biomass and Bioenergy, 2025)

Bioremediation enhancement by current-powered solenoid magnetic field in microbial fuel cell - Chyi-How Lay; Chalida Daengbussadee; Lakkana Laopaiboon; Yi-Chi Deng; Bedeny E. Wahby; Gopalakrishnan Kumar; Ponnusamy Vinoth Kumar; Setyo Budi Kurniawan; Peer Mohamed Abdul (World Journal of Microbiology and Biotechnology, 2025)

Assessment of the Indian Lightning Location Network (ILLN) using ground-based and satellite observations - Rupraj Biswasharma; Manoj A. Domkawale; Rakesh Ghosh; Abhijeet Gangane; N. Umakanth; Sunil Kumar; V. Gopalakrishnan; Sunil D. Pawar; Elizabeth DiGangi; Sachin M. Deshpande; Debajyoti Samanta; Sanjay Sharma (Atmospheric Research, 2025)

Lead-Induced Nephrotoxicity and Its Therapeutic Interventions: An Updated Review - Ankit Kumar Bharti S; Abilash Valsala Gopalakrishnan (Biological Trace Element Research, 2025)

Unlocking the Neuroprotective Potential of Silymarin: A Promising Ally in Safeguarding the Brain from Alzheimer’s Disease and Other Neurological Disorders - Abdulmajeed G. Almutary; M. Yasmin Begum; Ayesha Siddiqua; Saurabh Gupta; Payal Chauhan; Karan Wadhwa; Govind Singh; Danish Iqbal; Gopalakrishnan Padmapriya; Sanjay Kumar; Navin Kedia; Rajni Verma; et al. (Molecular Neurobiology, 2025)

Socio-economic status of commercial seaweed growers of Tamil Nadu, India after COVID-19 - V. Veeragurunathan; K. Sundaragnanam; P. Gwen Grace; S. GopalaKrishnan; V. Ajithkumar; S. Dinesh Kumar; Ramalingam Dineshkumar; Vaibhav A. Mantri (Journal of Applied Phycology, 2025)

Evaluation of Bcr/cflA Targeted Efflux Inhibitory Potential of 2-Hydroxy-4-Methoxybenzaldehyde Against Proteus mirabilis - Durgadevi Ravindran; Alexpandi Rajaiah; Roshini Swasthika; Prakash Balu; Abirami Gopalakrishnan; Ashok Kumar Krishna Kumar; Suganthi Muthusamy; Jayanthi Malayandi; Rohini Durairaj; Veera Ravi Arumugam (Indian Journal of Microbiology, 2025)

A critical review of biogas production and upgrading from organic wastes: Recent advances, challenges and opportunities - Veeramuthu Ashokkumar; Gopalakrishnan Kumar; Hariprasath Lakshmanan; V.P. Chandramughi; G. Flora; Richa Kothari; Grzegorz Piechota (Biomass and Bioenergy, 2025)

Impact of long-term seaweed (Kappaphycus alvarezii) aquaculture on species and functional diversity of macrobenthic communities in Southeastern coast, India - Moumita Bhowmik; Atanu Kumar Panja; U. Gurumoorthy; S. Gopalakrishnan; Veeragurunathan Veeraprakasam; Soumya Haldar (Aquaculture International, 2025)

Phytosociology and habitat suitability studies on Endemic jewel Orchid Aenhenrya rotundifolia in Southern Western Ghats, India - Subramanian Palaniyappan; Gopalakrishnan Aazhivaendhan; Rajendran Silambarasan; Noyaljohnson Tinoammini; Chinnaiyan Rajasekar; Thiruppathi Senthil Kumar (Vegetos, 2025)

From ocean to cage: evaluating the culture feasibility of Black-spotted croaker (Protonibea diacanthus) - Shubhadeep Ghosh; Gyanaranjan Dash; Biswajit Dash; Rajesh Kumar Pradhan; Sekar Megarajan; Pralaya Ranjan Behera; Ritesh Ranjan; Swatipriyanka Sen; Madhumita Das; Vettath Raghavan Suresh; Achamveetil Gopalakrishnan; Joykrushna Jena (Frontiers in Marine Science, 2025)
Introduction This study evaluates the feasibility of culturing the high-value marine fish Protonibea diacanthus in a polyculture system with Indian pompano ( Trachinotus mookalee ) using a marine cage culture setup. The study aims to determine growth performance, feed efficiency, and the potential of P. diacanthus as a candidate species for polyculture. Methods Wild-caught P. diacanthus were reared in six high-density polyethylene sea cages (Inner Diameter: 6 m; Outer Diameter: 7 m; Depth: 4.5 m; Area: 28.29 m²; Volume: 127.29 m³). Two experimental groups were established: Group-1 with 90 individuals (average weight: 130.15 ± 6.39 g) and Group-2 with 90 individuals (average weight: 287.80 ± 16.90 g). Each group was divided into three cages (30 fish/cage) and reared in triplicate with T. mookalee (2,500 fish/cage, average weight: 31.12 ± 1.17 g). The fish were cultured for 148 days and fed a commercial diet (40% crude protein, 10% crude lipid). Growth indices and feed efficiency indices were analyzed, and growth of the fish was modeled using von Bertalanffy Growth Function (VBGF). Results Growth performance indices, including total length gain, body weight gain, and specific growth rate, were significantly higher in Group-1 (P ≤ 0.05). Feed efficiency indices (feed conversion ratio, feed efficiency ratio, and protein efficiency ratio) did not differ significantly between the groups (P > 0.05). VBGF modeling estimated P. diacanthus asymptotic length (L ∞ ) at 164.21 ± 3.58 cm, asymptotic weight (W ∞ ) at 44,070.19 ± 2811 g, growth coefficient (K) at 0.30 ± 0.01 yr −1 and t₀ at -0.005 ± 0.02 yr. The growth performance index (ϕ’) was calculated at 1.91, surpassing values reported for wild populations. Polyculture with P. diacanthus did not significantly affect the growth or feed utilization of T. mookalee (P > 0.05). Discussion and conclusion The results indicate that P. diacanthus exhibits superior growth under marine cage culture conditions, with a high growth performance and compatibility in polyculture systems. These findings support the potential of P. diacanthus as a viable candidate for integration into commercial polyculture systems.

Thermodynamics link with lightning incidents in Tamil Nadu, India - S Kokilavani; V Geethalakshmi; S P Ramanathan; S D Pawar; V Gopalakrishnan; Somnath Mahapatra; Jayesh Chhagan Dhangar; Ga Dheebakaran; N K Sathyamoorthy; M Selva Kumar; S Mohan Kumar; Manoj A Domkawale (Journal of Earth System Science, 2024)

Evaluation and mitigation of potentially toxic elements contamination in mangrove ecosystem: Insights into phytoremediation and microbial perspective - Gobinda Dey; Jyoti Prakash Maity; Pritam Banerjee; Raju Kumar Sharma; Koyeli Das; Gopalakrishnan Gnanachandrasamy; Chin-Wen Wang; Pin-Yun Lin; Shan-Li Wang; Chien-Yen Chen (Marine Pollution Bulletin, 2024)

Exploring structural effect on the non-covalent interactions in binary mixtures of amines with cyclic ethers - N Mohamed Nasrullah; V Karthikeyan; N Gopalakrishnan; R Kumar; M Mohamed Naseer Ali; V Kannappan (Next Research, 2024)

Industrial–scale production of various bio–commodities by engineered microbial cell factories: Strategies of engineering in microbial robustness - Ju-Hyeong Jung; Vinoth Kumar Ponnusamy; Gopalakrishnan Kumar; Bartłomiej Igliński; Vinod Kumar; Grzegorz Piechota (Chemical Engineering Journal, 2024)

Helicobacter pylori biofilm interference by N-acyl homoserine lactonases: in vitro and in silico approaches - Vinoj Gopalakrishnan; Vaijayanthi Saravanan; Maria Infant Majula Shifani Mahendran; Madhana Priya Nanda Kumar (Molecular Biology Reports, 2024)

Analysis of tropical cloud-to-ground and intra-cloud lightning activity in southern India - C K Unnikrishnan; G R Malavika; Abhinav Kumar Shukla; V C Mobin Raj; V Gopalakrishnan; S D Pawar (Journal of Earth System Science, 2024)

Comprehensive techno-economic and environmental assessment for 2,3-butanediol production from bread waste - Bikash R Tiwari; Sunil K. Maity; Satinder K Brar; Kit Wayne Chew; Gopalakrishnan Kumar; Vinod Kumar (Chemical Engineering Journal, 2024)

Removal of nitrogen from wastewater: Unsolved problems and possible solutions with partial denitrification/anammox systems - Joanna Majtacz; Hussein E. Al-Hazmi; Xianbao Xu; Grzegorz Piechota; Xiang Li; Gopalakrishnan Kumar; Tejraj M. Aminabhavi; Mohammad Reza Saeb; Michael Badawi; Jacek Mąkinia (Chemical Engineering Journal, 2024)

Hydrochar as a bio-based adsorbent for heavy metals removal: A review of production processes, adsorption mechanisms, kinetic models, regeneration and reusability - Aisha Khan Khanzada; Hussein E. Al-Hazmi; Tonni Agustiono Kurniawan; Joanna Majtacz; Grzegorz Piechota; Gopalakrishnan Kumar; Peyman Ezzati; Mohammad Reza Saeb; Navid Rabiee; Hassan Karimi-Maleh; Eder Claudio Lima; Jacek Mąkinia (Science of The Total Environment, 2024)

Cutting-edge advances in alga Botryococcus for eco-friendly biofuels and high-value bioproducts — A critical review - Veeramuthu Ashokkumar; G. Flora; Gopalakrishnan Kumar; Wei-Hsin Chen; Grzegorz Piechota; Chyi-How Lay; Vinoth Kumar Ponnusamy; Chawalit Ngamcharussrivichai (Algal Research, 2024)

Biohydrogen upgradation and wastewater treatment in 3-chambered bioelectrochemical system assisted with H2/O2-based redox reactions - Dipak A. Jadhav; Gopalakrishnan Kumar; Jae Kyung Jang; Kyu-Jung Chae (Journal of Environmental Management, 2024)

First record of the rare deep-sea shark, Scymnodon ichiharai Yano and Tanaka, 1984 (Squaliformes: Somniosidae) from Andaman Waters, India - Ravi Ranjan Kumar; S. Venu; K. K. Bineesh; K. A. Sajeela; D. A. Ebert; A. Gopalakrishnan; V. S. Basheer (Thalassas: An International Journal of Marine Sciences, 2024)

Integrated microalgae cultivation and sustainable biofuel production from pretreated food waste - S. Kavitha; Yukesh Kannah Ravi; Gopalakrishnan Kumar; Vinay Kumar Tyagi; J. Rajesh Banu (Journal of Cleaner Production, 2024)

Correction: Association of Biochemical Parameters and Screening for Mutations in the MCU Gene in Alzheimer’s Disease Patients - Anila Venugopal; Mahalaxmi Iyer; Arul Narayanasamy; T. Ravimanickam; Abilash Valsala Gopalakrishnan; Mukesh Kumar Yadav; Nachimuthu Senthil Kumar; Balachandar Vellingiri (Molecular Neurobiology, 2024)

Association of Biochemical Parameters and Screening for Mutations in the MCU Gene in Alzheimer’s Disease Patients - Anila Venugopal; Mahalaxmi Iyer; Arul Narayanasamy; T Ravimanickam; Abilash Valsala Gopalakrishnan; Mukesh Kumar Yadav; Nachimuthu Senthil Kumar; Balachandar Vellingiri (Molecular Neurobiology, 2024)

Association Study Between Kynurenine 3-Monooxygenase (KMO) Gene and Parkinson’s Disease Patients - Harysh Winster Suresh Babu; Ajay Elangovan; Mahalaxmi Iyer; Laxmi Kirola; Sureshan Muthusamy; Priyanka Jeeth; Sindduja Muthukumar; Harvey Vanlalpeka; Abilash Valsala Gopalakrishnan; Saraboji Kadhirvel; Nachimuthu Senthil Kumar; Balachandar Vellingiri (Molecular Neurobiology, 2024)

Advancements in lignocellulosic biomass: A critical appraisal of fourth-generation biofuels and value-added bioproduct - Veeramuthu Ashokkumar; V.P. Chandramughi; Gopalakrishnan Kumar; Chawalit Ngamcharussrivichai; Grzegorz Piechota; Bartłomiej Igliński; Richa Kothari; Wei-Hsin Chen (Fuel, 2024)

Photosynthesis and radiation use efficiency at anthesis in relation to biomass accumulation and yield in Basmati rice (Oryza sativa L.) - Payal Priyadarsini; Madan Pal; Rakesh Pandey; S. Gopalakrishnan; Vinay Kumar Sehgal; Viswanathan Chinnusamy; Sukumar Taria; Pramod Kumar; Jasdeep Padaria; Milan Kumar Lal (Plant Physiology Reports, 2024)

Piperlongumine: the amazing amide alkaloid from Piper in the treatment of breast cancer - Shatakshi Mitra; Protha Biswas; Anupriya Bandyopadhyay; Vijaykumar Shivaji Gadekar; Abilash Valsala Gopalakrishnan; Manoj Kumar; Radha; Samapika Nandy (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Facile fabrication of amorphous Al/Fe based metal–organic framework as effective heterogeneous fenton catalyst for environmental remediation - Thirumoorthy Kulandaivel; Akshaya Subhramaniyan Rasappan; Kirankumar Venkatesan Savunthari; Melvin S. Samuel; Mohanraj Kumar; Hans-Uwe Dahms; Aswin Kumar Anbalagan; Gopalakrishnan Mohan; Soorathep Kheawhom; Sivarasan Ganesan (Environmental Geochemistry and Health, 2024)

Thermal tolerance and environment adaptability of Indian pompano: Discovery of a resilient candidate species for sustainable mariculture production in a climate change scenario - Damodaran Nair Divu; Suresh Kumar Mojjada; Mathavankonathu Kuttan Anil; Ambarish Purackattu Gopidas; Swathi Lekshmi Perumal Sundaram; Anbarasu Mahalingam; Muktha Menon; Ratheesh Kumar Raveendran; Ramesh Kumar Mojjada; Mayur Shivdas Tade; Jai Shree; Aarsha Subramanian; et al. (Aquaculture, 2024)

Energy efficiency and economics of small-scale fisheries (SSF) in India: A VIKOR based multicriteria decision-making model for sustainable fisheries management - Swathi Lekshmi Perumal Sundaram; Kalidoss Radhakrishnan; R. Narayanakumar; Vipin Kumar V. P; S. Surya; D. Divu; Nikita Gopal; Jose Kingsly; V.A. Leslie; Suresh Kumar Mojjada; Mayur Shivdas Tade; Aarsha Subramanian; et al. (Journal of Cleaner Production, 2024)

Forest Characterization Using C-band SAR Data—Initial Results of EOS-04 Data - Jayant Singhal; Tanumi Kumar; Rakesh Fararoda; Prabir Kumar Das; Rakesh Paliwal; Sudhakar Reddy Chintala; Gopalakrishnan Rajashekar (Journal of the Indian Society of Remote Sensing, 2024)

Non-Destructive Allometric Modeling for Tree Volume Estimation in Tropical Dry Deciduous Forests of India Using Terrestrial Laser Scanner - Suraj Reddy Rodda; Rama Rao Nidamanuri; T. Mayamanikandan; Gopalakrishnan Rajashekar; Chandra Shekar Jha; Vinay Kumar Dadhwal (Journal of the Indian Society of Remote Sensing, 2024)

Economic performance and marine policy implications of mud spiny lobster mariculture in Tropical Sea Cages, North-Eastern Arabian Sea, India: An empirical study in marine economics - Damodaran Nair Divu; Suresh Kumar Mojjada; Pratheesh Omana Sudhakaran; Swathi Lekshmi Perumal Sundaram; Muktha Menon; Ramesh Kumar Mojjada; Mayur Shivdas Tade; Vinuja Syamala Vishwambharan; Jai Shree; Aarsha Subramanian; Boby Ignatius; Achamveetil Gopalakrishnan (Marine Policy, 2024)

First report of clinically significant bites due to Platyceps ventromaculatus (GRAY, 1834) from Thar Desert region, Rajasthan, India - Akhilesh Kumar; Sourish Kuttalam; Divya Tanwar; Bharat Choudhary; Mahendra Kumar Garg; Maya Gopalakrishnan (Toxicon, 2024)

Association of lightning with LCL, EL, humidity at 850 mb and at 200 mb during various CAPE, over northern India - Deen Mani Lal; Nandivada Umakanth; Manoj Arjun Domkawale; Venkatachalam Gopalakrishnan; Manoj Kumar Srivastava; Sunil Dnyandeo Pawar (Science of The Total Environment, 2024)

Corrigendum to “a review of chromium (Cr) epigenetic toxicity and health hazards” [Sci. Total environ., volume 882, 1–12, 15 July 2023, 163,483] - Mahalaxmi Iyer; Uttpal Anand; Saranya Thiruvenkataswamy; Harysh Winster Suresh Babu; Arul Narayanasamy; Vijay Kumar Prajapati; Chandan Kumar Tiwari; Abilash Valsala Gopalakrishnan; Elza Bontempi; Christian Sonne; Damià Barceló; Balachandar Vellingiri (Science of The Total Environment, 2024)

Understanding microplastic pollution: Tracing the footprints and eco-friendly solutions - Shashi Kant Bhatia; Gopalakrishnan Kumar; Yung-Hun Yang (Science of The Total Environment, 2024)

Invitro germination and optimization of basal media for protocorm-like bodies proliferation in Dienia ophrydis (J. Koenig) Seidenf - Noyaljohnson Tinoammini; Gopalakrishnan Aazhivaendhan; Thiruppathi Senthil Kumar (Rhizosphere, 2024)

Interface engineering of heterogeneous NiMn layered double hydroxide/vertically aligned NiCo2S4 nanosheet as highly efficient hybrid electrocatalyst for overall seawater splitting - S. Gopalakrishnan; G. Anandha babu; S. Harish; E. Senthil Kumar; M. Navaneethan (Chemosphere, 2024)

An integrated techno-economic decision-support fiscal forecast model for sea cage mariculture enterprises for Asian seabass production in Indian territorial waters - Suresh Kumar Mojjada; Damodaran Nair Divu; Prateesh Omna Sudhakaran; Swathi Lekshmi Perumal Sundaram; Muktha Menon; Ramesh Kumar Mojjada; Mayur Shivdas Tade; Vinuja Syamala Viswambharan; Jai Shree; Aarsha Subramanian; Suresh Vettath Raghavan; Achamveetil Gopalakrishnan (Aquaculture, 2024)

Microalgal biorefineries: Advancement in machine learning tools for sustainable biofuel production and value-added products recovery - Kavitha S; Yukesh Kannah Ravi; Gopalakrishnan Kumar; Yogalakshmi Kadapakkam Nandabalan; Rajesh Banu J (Journal of Environmental Management, 2024)

Co-infection of mud crab Reovirus (MCRV) and Staphylococcus saprophyticus in giant mud crab, Scylla serrata (Forsskal, 1775) - Anisha Shafni John; Ayyaru Gopalakrishnan; Savva Sravani; Naresh Kumar Dewangan; Muhil Vannan Seralathan; Narayanasamy Marimuthu Prabhu (Aquaculture, 2024)

Spatial variation of the broodstock availability of Acanthopagrus berda (Forsskal 1775) with emphasis on seasonality, lunar periodicity, and sex ratio for facilitating efficient breeding program - Suresh Babu Padinhate Purayil; Shilta Madathumpady Thomas; Rajan Kumar; Anuraj Anirudhan; Narayan Dube Praveen; Vaidya Narayan Gopal; Prathibha Rohit; Gopalakrishnan Achamveetil (Regional Studies in Marine Science, 2024)

Calcium peroxide induced mechanical disintegration in acidic environment for efficient biogas and biopolymer generation from paper mill sludge - Preethi; J. Rajesh Banu; Gopalakrishnan Kumar; M. Gunasekaran (Fuel, 2024)

Recent progress in mineralization of emerging contaminants by advanced oxidation process: A review - Preethi; Surya Prakash Shanmugavel; Gopalakrishnan Kumar; Yogalakshmi K. N; Gunasekaran M; Rajesh Banu J (Environmental Pollution, 2024)

Biomass based biochar production approaches and its applications in wastewater treatment, machine learning and microbial sensors - Si-Kyung Cho; Bartłomiej Igliński; Gopalakrishnan Kumar (Bioresource Technology, 2024)

Assessment of tRNAThr and tRNAGln Variants and Mitochondrial Functionality in Parkinson’s Disease (PD) Patients of Tamil Nadu Population - Dhivya Venkatesan; Mahalaxmi Iyer; Neethu Raj; Abilash Valsala Gopalakrishnan; Arul Narayanasamy; Nachimuthu Senthil Kumar; Balachandar Vellingiri (Journal of Molecular Neuroscience, 2023)

Green chemical and hybrid enzymatic pretreatments for lignocellulosic biorefineries: Mechanism and challenges - Rijuta Ganesh Saratale; Vinoth Kumar Ponnusamy; Grzegorz Piechota; Bartłomiej Igliński; S. Shobana; Jeong-Hoon Park; Ganesh Dattatraya Saratale; Han Seung Shin; J. Rajesh Banu; Vinod Kumar; Gopalakrishnan Kumar (Bioresource Technology, 2023)

Effect of thermal-calcium peroxide mediated exopolymer release on disperser pre-treatment for efficient anaerobic digestion - Sivaraman Chandrasekaran; J. Rajesh Banu; Gopalakrishnan Kumar (Environmental Research, 2023)

Fruit peel bioactives, valorisation into nanoparticles and potential applications: A review - Rajat Suhag; Rohit Kumar; Atul Dhiman; Arun Sharma; Pramod K. Prabhakar; Krishna Gopalakrishnan; Ritesh Kumar; Anurag Singh (Critical Reviews in Food Science and Nutrition, 2023)

Exploring biophysical links of catch rate from mid-water trawl fishery in the north-west coast of India, Eastern Arabian Sea: A remote sensing approach - Pokkathappada Abdul Azeez; Prathibha Rohit; Mini Raman; Latha Shenoy; Ashok Kumar Jaiswar; Kunnamgalam Mohammed Koya; Suresh K. Mojjada; Divu Damodaran; Achamveetil Gopalakrishnan (Science of The Total Environment, 2023)

Current approaches, and challenges on identification, remediation and potential risks of emerging plastic contaminants: A review - Huy Hoang Phan Quang; Duc Anh Dinh; Vishal Dutta; Ankush Chauhan; Sudip Kumar Lahiri; C. Gopalakrishnan; Arunkumar Radhakrishnan; Khalid Mujasam Batoo; Lan-Anh Phan Thi (Environmental Toxicology and Pharmacology, 2023)

Oxidative torrefaction of microalgae Chlorella sorokiniana: Process optimization by central composite design - Charles B. Felix; Wei-Hsin Chen; Jo-Shu Chang; Young-Kwon Park; Samrand Saeidi; Gopalakrishnan Kumar (Bioresource Technology, 2023)

Cost-effective bio-methanation via oxalic acid coupled sonication pretreatment of Gracilaria salicornia - Rashmi Gondi; Akila; Yukesh Kannah Ravi; S. Kavitha; Siham Y. Al-Qaradawi; Dinakar Challabathula; Gopalakrishnan Kumar; J. Rajesh Banu (Biomass and Bioenergy, 2023)

Type 2 Diabetes (T2DM) and Parkinson’s Disease (PD): a Mechanistic Approach - S. Sri Sabari; Kiruthika Balasubramani; Mahalaxmi Iyer; Harysh Winster Sureshbabu; Dhivya Venkatesan; Abilash Valsala Gopalakrishnan; Arul Narayanaswamy; Nachimuthu Senthil Kumar; Balachandar Vellingiri (Molecular Neurobiology, 2023)

Fermentative valorisation of xylose-rich hemicellulosic hydrolysates from agricultural waste residues for lactic acid production under non-sterile conditions - Rylan Cox; Vivek Narisetty; Eulogio Castro; Deepti Agrawal; Samuel Jacob; Gopalakrishnan Kumar; Deepak Kumar; Vinod Kumar (Waste Management, 2023)

A review of chromium (Cr) epigenetic toxicity and health hazards - Mahalaxmi Iyer; Uttpal Anand; Saranya Thiruvenkataswamy; Harysh Winster Suresh Babu; Arul Narayanasamy; Vijay Kumar Prajapati; Chandan Kumar Tiwari; Abilash Valsala Gopalakrishnan; Elza Bontempi; Christian Sonne; Damià Barceló; Balachandar Vellingiri (Science of The Total Environment, 2023)

A review on the pollution assessment of hazardous materials and the resultant biorefinery products in Palm oil mill effluent - Anu Alias Meena R; Merrylin J; Rajesh Banu J; Shashi Kant Bhatia; Vinod Kumar; Grzegorz Piechota; Gopalakrishnan Kumar (Environmental Pollution, 2023)

Deciphering the melatonin-mediated response and signalling in the regulation of heavy metal stress in plants - Muhammad Ahsan Altaf; Nitin Sharma; Dipali Srivastava; Sayanti Mandal; Sandeep Adavi; Rupak Jena; Rakesh Kumar Bairwa; Abilash Valsala Gopalakrishnan; Awadhesh Kumar; Abhijit Dey; Milan Kumar Lal; Rahul Kumar Tiwari; et al. (Planta, 2023)

Correction: Concurrent Assessment of Oxidative Stress and MT-ATP6 Gene Profiling to Facilitate Diagnosis of Autism Spectrum Disorder (ASD) in Tamil Nadu Population - Balachandar Vellingiri; Dhivya Venkatesan; Mahalaxmi Iyer; Gomathi Mohan; Padmavathi Krishnan; Krothapalli Sai Krishna; Sangeetha R; Arul Narayanasamy; Abilash Valsala Gopalakrishnan; Nachimuthu Senthil Kumar; Mohana Devi Subramaniam (Journal of Molecular Neuroscience, 2023)

A novel decision-support system for augmenting sustainable lobster production through comparison of mariculture systems at increasing stages of technological development - Damodaran Nair Divu; Suresh Kumar Mojjada; Gyanaranjan Dash; Swathi Lekshmi Perumal Sundaram; Muktha Menon; Mayur Shivdas Tade; Ramesh Kumar Mojjada; Hiralal Mepabhai Bhint; Jaishree Bhardwaj; Aarsha Subramanian; Vettath Raghavan Suresh; Achamveetil Gopalakrishnan (Journal of Cleaner Production, 2023)

Biogenic fluorescent carbon dots modulated fabrication of concatenate logic library and pattern-mediated molecular keypad lock for chemical sensing application - Ajith Manayil Parambil; Mohamed Nabeel Mattath; Paulraj Rajamani; Phuong V. Pham; Gopalakrishnan Kumar; Vinoth Kumar Ponnusamy (Chemical Engineering Journal, 2023)

Combined sodium citrate and ultrasonic pretreatment of waste activated sludge for cost effective production of biogas - J. Rajesh Banu; S. Kavitha; Yukesh Kannah Ravi; Vinay Kumar Tyagi; Gopalakrishnan Kumar (Bioresource Technology, 2023)

Mangiferin: the miraculous xanthone with diverse pharmacological properties - Tusheema Dutta; Tuyelee Das; Abilash Valsala Gopalakrishnan; Suchismita Chatterjee Saha; Mimosa Ghorai; Samapika Nandy; Manoj Kumar; Radha; Arabinda Ghosh; Nobendu Mukerjee; Abhijit Dey (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Concurrent Assessment of Oxidative Stress and MT-ATP6 Gene Profiling to Facilitate Diagnosis of Autism Spectrum Disorder (ASD) in Tamil Nadu Population - Balachandar Vellingiri; Dhivya Venkatesan; Mahalaxmi Iyer; Gomathi Mohan; Padmavathi Krishnan; Krothapalli Sai Krishna; Sangeetha R; Arul Narayanasamy; Abilash Valsala Gopalakrishnan; Nachimuthu Senthil Kumar; Mohana Devi Subramaniam (Journal of Molecular Neuroscience, 2023)

Jellyfish fisheries along the Gujarat coast, India: Status and challenges - Tarachand Kumawat; Raju Saravanan; Kavungal Vinod; Ashok Kumar Jaiswar; Geetanjali Deshmukhe; Latha Shenoy; Damodaran Divu; Kunnummel Krishnan Joshi; Achamveetil Gopalakrishnan (Marine Policy, 2023)

Microalgae gasification over Ni loaded perovskites for enhanced biohydrogen generation - Soheil Valizadeh; Yasin Khani; Abid Farooq; Gopalakrishnan Kumar; Pau Loke Show; Wei-Hsin Chen; See Hoon Lee; Young-Kwon Park (Bioresource Technology, 2023)

Bread waste – A potential feedstock for sustainable circular biorefineries - Vinod Kumar; Pedro Brancoli; Vivek Narisetty; Stephen Wallace; Dimitris Charalampopoulos; Brajesh Kumar Dubey; Gopalakrishnan Kumar; Amit Bhatnagar; Shashi Kant Bhatia; Mohammad J. Taherzadeh (Bioresource Technology, 2023)

A review on current advances in the energy and cost effective pretreatments of algal biomass: Enhancement in liquefaction and biofuel recovery - S. Kavitha; Rashmi Gondi; R. Yukesh Kannah; Gopalakrishnan Kumar; J. Rajesh Banu (Bioresource Technology, 2023)

Augmentation in polyhydroxybutyrate and biogas production from waste activated sludge through mild sonication induced thermo-fenton disintegration - Preethi; J. Rajesh Banu; Gopalakrishnan kumar; M. Gunasekaran (Bioresource Technology, 2023)

Lignocellulosic biomass conversion via greener pretreatment methods towards biorefinery applications - Jeyaprakash Dharmaraja; Sutha Shobana; Sundaram Arvindnarayan; Rusal Raj Francis; Rajesh Banu Jeyakumar; Rijuta Ganesh Saratale; Veeramuthu Ashokkumar; Shashi Kant Bhatia; Vinod Kumar; Gopalakrishnan Kumar (Bioresource Technology, 2023)

Unravelling the pharmacological properties of cryptolepine and its derivatives: a mini-review insight - Champa Keeya Tudu; Anustup Bandyopadhyay; Manoj Kumar; Radha; Tuyelee Das; Samapika Nandy; Mimosa Ghorai; Abilash Valsala Gopalakrishnan; Jarosław Proćków; Abhijit Dey (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Cryptolepine (1,5-methyl-10 H -indolo[3,2- b ]quinoline), an indoloquinoline alkaloid, found in the roots of Cryptolepis sanguinolenta (Lindl.) Schltr (family: Periplocaceae), is associated with the suppression of cancer and protozoal infections. Cryptolepine also exhibits anti-bacterial, anti-fungal, anti-hyperglycemic, antidiabetic, anti-inflammatory, anti-hypotensive, antipyretic, and antimuscarinic properties. This review of the latest research data can be exploited to create a basis for the discovery of new cryptolepine-based drugs and their analogues in the near future. PubMed, Scopus, and Google Scholar databases were searched to select and collect data from the existing literature on cryptolepine and their pharmacological properties. Several in vitro studies have demonstrated the potential of cryptolepine A as an anticancer and antimalarial molecule, which is achieved through inhibiting DNA synthesis and topoisomerase II. This review summarizes the recent developments of cryptolepine pharmacological properties and functional mechanisms, providing information for future research on this natural product.

Population genetic research on the Spadenose shark, Scoliodon laticaudus (Chondrichthyes, Carcharhinidae), reveals the presence of two significantly differentiated clades along the Indian coast - Sandhya Sukumaran; Wilson Sebastian; P. U. Zacharia; Shoba J. Kizhakudan; K. V. Akhilesh; Sujitha Thomas; Subal Kumar Roul; M. Muktha; Swati Priyanka Sen; G. B. Purushottama; Shikha Rahangdale; K. K. Bineesh; et al. (Marine Biodiversity, 2023)

Spent coffee grounds anaerobic digestion: Investigating substrate to inoculum ratio and dilute acid thermal pretreatment - Georgeio Semaan; M.R. Atelge; Roent Dune Cayetano; Gopalakrishnan Kumar; Roald Kommedal (Fuel, 2023)

Valorization of nano-based lignocellulosic derivatives to procure commercially significant value-added products for biomedical applications - Vickram AS; Gopalakrishnan Kumar; Nibedita Dey; Rohini Karunakaran; Anbarasu K; Anil Kumar Patel; Thanigaivel S; Gangadhar Andaluri; Yuan-Chung Lin; Deena Santhana Raj; Vinoth Kumar Ponnusamy (Environmental Research, 2023)

Algal biomass to biohydrogen: Pretreatment, influencing factors, and conversion strategies - Shashi Kant Bhatia; J. Rajesh Banu; Vijai Singh; Gopalakrishnan Kumar; Yung-Hun Yang (Bioresource Technology, 2023)

Recent advances in biowaste management towards sustainable environment - Grzegorz Piechota; Yuwalee Unpaprom; Cheng–Di Dong; Gopalakrishnan Kumar (Bioresource Technology, 2023)

Technological advances in the production of carotenoids and their applications– A critical review - Veeramuthu Ashokkumar; G. Flora; Murugan Sevanan; R. Sripriya; W.H Chen; Jeong-Hoon Park; J. Rajesh banu; Gopalakrishnan Kumar (Bioresource Technology, 2023)

Resolved and Redeemed: A New Fleck to the Evolutionary Divergence in the Genus Scomberomorus Lacepède, 1801 (Scombridae) With Cryptic Speciation - N. S. Jeena; Summaya Rahuman; Subal Kumar Roul; P. Abdul Azeez; R. Vinothkumar; H. M. Manas; E. A. Nesnas; A. Margaret Muthu Rathinam; S. Surya; Prathibha Rohit; E. M. Abdussamad; A. Gopalakrishnan (Frontiers in Marine Science, 2022)
The genus Scomberomorus , with 18 nominal species, sustains a significant heterogeneous fishery throughout its range. The sole molecular systematic study of this genus concerned the species group S. regalis , which contains the new world taxa. The species diversity of Scomberomorus in the northern Indian Ocean has not been studied at the molecular level, often leading to misidentifications. Here, novel genetic data are provided that reconfigure species boundaries from the region. We used single and multilocus data (eight mitochondrial and three nuclear genes) to infer phylogenetic relationships, species delimitation, and the resurrection of a time-calibrated phylogenetic tree. Our aim was also to verify the hypothesis of geographical races in S. guttatus predicated on variable vertebral counts. Interestingly, all species delimitation analyses have recovered another highly cryptic species in the nominal S. guttatus previously believed to have an Indo-Pacific distribution . Scomberomorus guttatus (Bloch and Schneider, 1801) in the sensu stricto , is redeemed from its type locality based on genetic data and preliminary morphomeristic investigations and has a restricted distribution in the Bay of Bengal. The cryptic species Scomberomorus aff. guttatus which exhibits >10% genetic divergence from S. guttatus is resurrected here from the synonymy of the latter as Scomberomorus leopardus (Shaw, 1803). Widespread in the Indo-Pacific, this species contains two major molecular operational taxonomic units (MOTUs) with a divergence threshold of over 2% between them. Our analysis suggests that vertebral counts must be coupled with other features to identify the species/lineages in the nominal S. guttatus. The heterogeneity in the S. guttatus species group is discussed in relation to the ecological diversity of the region which facilitates larval recruitment and niche specialization. The results also revealed two allopatric putative species in S. commerson , found primarily in the Pacific and Indian Oceans. This study added genetic data from S. lineolatus and S. koreanus , not previously represented in the sequence repositories. Estimation of divergence time indicated that the Indo-West Pacific species group undergoes multiple diversification events besides the recent splits detected within S . leopardus .

Evapotranspiration Modeling Using Different Tree Based Ensembled Machine Learning Algorithm - Yash Agrawal; Manoranjan Kumar; Supriya Ananthakrishnan; Gopalakrishnan Kumarapuram (Water Resources Management, 2022)

Postulating the Modality of Integrative Taxonomy in Describing the Cryptic Congener Pampus griseus (Cuvier) and Systematics of the Genus Pampus (Perciformes: Stromateidae) - Subal Kumar Roul; N. S. Jeena; Rajan Kumar; R. Vinothkumar; Shikha Rahangdale; Summaya Rahuman; Shubhadeep Ghosh; Prathibha Rohit; Achamveetil Gopalakrishnan (Frontiers in Marine Science, 2021)
Pomfrets (genus Pampus ), a highly commercial fishery resource distributed in the Indo-Western Pacific that includes Lessepsian migrants, have witnessed a series of systematic reforms. In this study, based on comprehensive sampling spanning type localities and coevals in the Northern Indian Ocean, the cryptic and valid species Stromateus griseus is resurrected from the synonymy and re-described as Pampus griseus (New Combination) based on 35 specimens from the Bay of Bengal, corroborated by a molecular analysis, which indicated a confined distribution of the species. The Bayesian phylogeny of the genus was reconstructed, incorporating redressed barcodes (582 nucleotides) and concatenated mitochondrial gene sequence data (1,822 nucleotides) generated from the recorded species P . candidus , P . chinensis and the neophyte along with sequences from GenBank entrusting the latest literature. The phylograms differed in topology as for seven valid species, and the one predicated on the concatenated data erected a highly supported polytomous clade for the P . cinereus complex ( P . griseus , P . cinereus , and P . candidus ) which shares synapomorphies. Pampus argenteus and P . minor , together, formed a sister clade to the rest. Climate-driven vicariant events during glacial epochs and the Indo-Pacific Barrier effect can be the drivers behind the Indian and Pacific Ocean sister lineages in P . chinensis . A multivariate analysis isolated the cryptic species from its congeners. This article portrays the systematics revision of genus Pampus with an integrative taxonomic approach compiling distinctive molecular, morphological, and anatomical features, revised key for species identification, taxonomic archives of Indian stromateids, and winds up with specific remarks.

Bioelectrochemical system-mediated waste valorization - K. Chandrasekhar; A. Naresh Kumar; Tirath Raj; Gopalakrishnan Kumar; Sang-Hyoun Kim (Systems Microbiology and Biomanufacturing, 2021)
Bioelectrochemical systems (BESs) are a new and emerging technology in the field of fermentation technology. Electrical energy was provided externally to the microbial electrolysis cells (MECs) to generate hydrogen or value-added chemicals, including caustic, formic acid, acetic acid, and peroxide. Also, BES was designed to recover nutrients, metals or remove recalcitrant compounds. The variety of naturally existing microorganisms and enzymes act as a biocatalyst to induce potential differences amid the electrodes. BESs can be performed with non-catalyzed electrodes (both anode and cathode) under favorable circumstances, unlike conventional fuel cells. In recent years, value-added chemical producing microbial electrosynthesis (MES) technology has intensely broadened the prospect for BES. An additional strategy includes the introduction of innovative technologies that help with the manufacturing of alternative materials for electrode preparation, ion-exchange membranes, and pioneering designs. Because of this, BES is emerging as a promising technology. This article deliberates recent signs of progress in BESs so far, focusing on their diverse applications beyond electricity generation and resulting performance.

Trends in Biological Nutrient Removal for the Treatment of Low Strength Organic Wastewaters - J Rajesh Banu; J Merrylin; S Kavitha; R Yukesh Kannah; P Selvakumar; S Gopikumar; P Sivashanmugam; Khac-Uan Do; Gopalakrishnan Kumar (Current Pollution Reports, 2021)

Antifungal and defense elicitor activities of pyrazines identified in endophytic Pseudomonas putida BP25 against fungal blast incited by Magnaporthe oryzae in rice - Asharani Patel; Aundy Kumar; Neelam Sheoran; Mukesh Kumar; Kuleshwar Prasad Sahu; Prakash Ganeshan; Mushineni Ashajyothi; Subbaiyan Gopalakrishnan; Robin Gogoi (Journal of Plant Diseases and Protection, 2021)

Adsorption, degradation, and mineralization of emerging pollutants (pharmaceuticals and agrochemicals) by nanostructures: a comprehensive review - Monika Jain; Ackmez Mudhoo; Deepika Lakshmi Ramasamy; Mahsa Najafi; Muhammad Usman; Runliang Zhu; Gopalakrishnan Kumar; Sutha Shobana; Vinod Kumar Garg; Mika Sillanpää (Environmental Science and Pollution Research, 2020)

Resource recovery from wastewater, solid waste, and waste gas: engineering and management aspects - Eldon R. Rene; Jinyi Ge; Gopalakrishnan Kumar; Rajendra Prasad Singh; Sunita Varjani (Environmental Science and Pollution Research, 2020)

Comparative evaluation of biochemical methane potential of various types of Ugandan agricultural biomass following soaking aqueous ammonia pretreatment - Abura Tobby Oliwit; Roent Dune A. Cayetano; Gopalakrishnan Kumar; Jun Seok Kim; Sang-Hyoun Kim (Environmental Science and Pollution Research, 2020)

Composting of Sweet Sorghum Bagasse and its Impact on Plant Growth Promotion - Subramaniam Gopalakrishnan; Vadlamudi Srinivas; Are Ashok Kumar; Akula V. Umakanth; Uma Addepally; Pinnamaneni Srinivasa Rao (Sugar Tech, 2020)

Microseismic monitoring application for primary stability evaluation of the powerhouse of the Tapovan Vishnugad Hydropower Project - Vikalp Kumar; N Gopalakrishnan; N P Singh; Sivakumar Cherukuri (Journal of Earth System Science, 2019)

Clinical efficacy and safety of cefepime–tazobactam in hospitalized patients in South India - Nitin Bansal; Kalpesh S Sukhwani; Suresh Kumar D; P. Senthur Nambi; Ram Gopalakrishnan; V Ramasubramanian (Infectious Diseases, 2018)

Bio-fabrication of silver nanoparticles using the leaf extract of an ancient herbal medicine, dandelion (Taraxacum officinale), evaluation of their antioxidant, anticancer potential, and antimicrobial activity against phytopathogens - Rijuta G. Saratale; Giovanni Benelli; Gopalakrishnan Kumar; Dong Su Kim; Ganesh D. Saratale (Environmental Science and Pollution Research, 2018)

Exploiting fruit byproducts for eco-friendly nanosynthesis: Citrus × clementina peel extract mediated fabrication of silver nanoparticles with high efficacy against microbial pathogens and rat glial tumor C6 cells - Rijuta Ganesh Saratale; Han-Seung Shin; Gopalakrishnan Kumar; Giovanni Benelli; Gajanan S. Ghodake; Yuan Yuan Jiang; Dong Su Kim; Ganesh Dattatraya Saratale (Environmental Science and Pollution Research, 2018)

The impact of assimilating MeghaTropiques SAPHIR radiances in the simulation of tropical cyclones over the Bay of Bengal using the WRF model - M. Dhanya; Deepak Gopalakrishnan; A. Chandrasekar; Sanjeev Kumar Singh; V.S. Prasad (International Journal of Remote Sensing, 2016)

Population genetic structure of the shovel-nosed lobster Thenus unimaculatus (Decapoda, Scyllaridae) in Indian waters based on RAPD and mitochondrial gene sequences - N. S. Jeena; A. Gopalakrishnan; J. K. Kizhakudan; E. V. Radhakrishnan; Raj Kumar; P. K. Asokan (Hydrobiologia, 2016)

Antioxidant potential of bilirubin-accelerated wound healing in streptozotocin-induced diabetic rats - Mahendra Ram; Vishakha Singh; Dhirendra Kumar; Sanjay Kumawat; Anu Gopalakrishnan; Madhu C. Lingaraju; Priyanka Gupta; Surendra Kumar Tandan; Dinesh Kumar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Barcoding of Asian seabass across its geographic range provides evidence for its bifurcation into two distinct species - Shubha Vij; Kathiresan Purushothaman; G. Gopikrishna; Doreen Lau; Jolly M. Saju; K. V. Shamsudheen; K. Vinaya Kumar; V. S. Basheer; A. Gopalakrishnan; Mohammad S. Hossain; Sridhar Sivasubbu; Vinod Scaria; et al. (Frontiers in Marine Science, 2014)

Mitochondrial ATPase 6/8 genes reveal genetic divergence in the Coilia dussumieri (Valenciennes, 1848) populations of north east and northwest coasts of India - A. Kathirvelpandian; A. Gopalakrishnan; W. S. Lakra; Gopal Krishna; Rupam Sharma; P. R. Divya; Raj Kumar; J. K. Jena (Molecular Biology Reports, 2014)

Assessment of different methods of rice (Oryza sativa. L) cultivation affecting growth parameters, soil chemical, biological, and microbiological properties, water saving, and grain yield in rice–rice system - Subramaniam Gopalakrishnan; R. Mahender Kumar; Pagidi Humayun; V. Srinivas; B. Ratna Kumari; R. Vijayabharathi; Amit Singh; K. Surekha; Ch. Padmavathi; N. Somashekar; P. Raghuveer Rao; P. C. Latha; et al. (Paddy and Water Environment, 2014)

Molecular characterization of eight Indian Snakehead species (Pisces: Perciformes Channidae) using RAPD markers - Ajaz Ali Bhat; M. A. Haniffa; P. R. Divya; A. Gopalakrishnan; M. James Milton; Raj Kumar; Bilal Ahmad Paray (Molecular Biology Reports, 2012)

Evaluation of bacteria isolated from rice rhizosphere for biological control of charcoal rot of sorghum caused by Macrophomina phaseolina (Tassi) Goid. - Subramaniam Gopalakrishnan; Pagidi Humayun; Bandru Keerthi Kiran; Iyer Girish Kumar Kannan; Meesala Sree Vidya; Kanala Deepthi; Om Rupela (World Journal of Microbiology and Biotechnology, 2011)

A macroeconomic analysis of adaptation to climate change impacts on forests in India - Asbjørn Aaheim; Ranjith Gopalakrishnan; Rajiv Kumar Chaturvedi; N. H. Ravindranath; Anitha D. Sagadevan; Nitasha Sharma; Taoyuan Wei (Mitigation and Adaptation Strategies for Global Change, 2011)

Genetic heterogeneity in the Indian stocks of seahorse (Hippocampus kuda and Hippocampus trimaculatus) inferred from mtDNA cytochrome b gene - Mukunda Goswami; Kumarasamy Thangaraj; Binod Kumar Chaudhary; L. V. S. K. Bhaskar; Achamveettil Gopalakrishnan; M. B. Joshi; Lalji Singh; Wazir S. Lakra (Hydrobiologia, 2009)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)